Linking production paradigms and organizational approaches to production systems - Silva, Sílvio Carmo (2006)
Manufacturing system design and operation is critical to achieve strategic company objectives. This must aim fitting manufacturing systems capabilities to the different demand market environments, having in consideration the different approaches and strategies that should be used. In this paper we develop a framework for characterizing production system conceptual models and linking them to both production paradigms and organizational approaches to production, such as lean and agile manufacturing. The conceptual models identified are useful for aiding to implement organizational approaches and fit manufacturing systems to manufacturing requirements determined by different product demand patterns.